Outdoor air pollution and hospitalizations for ischemic heart disease: a systematic review and meta-analysis - Maimaitiniyazi, Mailidan; Haibier, Abuduwupuer; Maimaitiniyazi, Muyesaier; Maisuti, Meiheliya; Aihaiti, Ailifeire; Yisimiti, Tuersunayi; Nijiati, Muyesai (Frontiers in Public Health, 2025)
ObjectiveThe study aimed to evaluate the association between six major outdoor air pollutants (i.e., PM2.5, PM10, NO2, SO2, CO, and O3) and the risk of ischemic heart disease (IHD)-attributable hospitalization to provide potential scientific evidence for the formulation of clinical and public health policies.MethodsUsing the PubMed and Web of Science databases (up to March 2025), the present meta-analysis screened and included 17 high-quality studies (three cohort studies (CS), one case–control study (CC), and 13 time-series studies (TS)) covering 28,186,905 cases hospitalized for IHD. This study focused on the determination of the impact of air pollutant concentration changes on the risk of IHD-attributable hospitalization using statistical analysis in Stata 16.0. In addition, sensitivity analyses and funnel plots were employed to assess stability and publication bias.ResultsThe meta-analysis revealed the following associations between the air pollutants and IHD-attributable hospitalization: PM2.5: [RR = 1.01 (95% confidence interval (CI):1.00 ~ 1.01), p = 0.000], PM10: [RR = 1.01 (95%CI:1.00 ~ 1.01), p = 0.000], NO2: [RR = 1.02 (95%CI: 1.00 ~ 1.03), p = 0.000], SO2: [RR = 1.01 (95%CI: 1.00 ~ 1.02), p = 0.001], CO: [RR = 1.04 (95%CI: 0.97 ~ 1.12), p = 0.01], and O3: [RR = 1.00 (95%CI: 1.00 ~ 1.00),p = 0.000].ConclusionHigh concentrations of air pollutants may significantly contribute to an increased risk of IHD-attributable hospitalization. The present study identifies air pollution as a major modifiable cardiovascular risk factor that should be integrated into clinical cardiovascular disease (CVD) management and public health policy formulation.